Kedudukan Alat Bukti dan Dinamika Beban Pembuktian pada Sengketa Pembayaran Kontrak Pemerintah: Studi Putusan Nomor 7/Pdt.G/2022/PN Tli - Wijaya, Laela Kuwayyis; Rahma, Nasya Nadhira; Tirajoh, Thenezia Tania; Ghifari, Tyazza Amaranila (VISA: Journal of Vision and Ideas, 2025)
This research aims to analyze the position of evidence and the dynamics of the burden of proof in disputes over government contract payments, with a focus on their implications for legal protection of business actors and the effectiveness of state budget implementation. The method used is a case study of District Court Decision No. 7/Pdt.G/2022/PN Tolitoli, involving a lawsuit filed by a private company against the local government for default in paying the remaining budget of a public market construction project in the 2018 fiscal year. The analysis is conducted normatively by examining contract documents, amendments, proof of work completion, and correspondence between the parties, as well as the evidentiary dynamics between the plaintiff and the defendant, including public officials and central government agencies. The findings reveal that the court acknowledged the validity of the contract and its amendments as primary evidence, declared the defendant in default for failing to fulfill payment obligations despite the completion of the project, and partially granted the plaintiff’s claim while rejecting the defendant’s administrative objection. Written evidence dominated the evidentiary process, while the burden of proof shifted from the plaintiff to the defendant once the initial evidence was presented, underscoring the principle that a valid agreement binds the parties and cannot be avoided on bureaucratic grounds. In conclusion, this decision reinforces both substantive and formal evidentiary practices in civil cases, promotes transparency and accountability in government contracts, protects business actors from the risks of default, and enhances legal certainty in state budget management to support a fairer and more professional bureaucratic reform.